THE TRANSITION SAGA OF MASCULINITY IN HINDI FILMS : THEN & NOW - Chowdhary, Ruchita Sujai (International Journal of Research -GRANTHAALAYAH, 2021)
The cinema in India has its different mark upon the masses and has a huge fan following. Being the most popular art form in the nation it has been influencing the viewers with its magical effects. With its tremendous reach among the youths it not only depict the virtual image of the society but on the same hand it is creating a world which is juxtapose of realm. Since the beginning Hindi films are revolving around the set plots of the scripted feature films showcasing a hero, a heroine, a villain and a climax after which everybody has a happy ending. Accordingly, the Hindi films have defined the heroes in its own way with some set parameters i.e. muscular body, taller than heroine, a fighter, good looks and a never ending list of traits. However, some heroes have broken this myth that a filmy hero is always a MACHO MAN. They are again redefining the personality of the heroes on the silverscreen. Thus, the aim of this research paper is to examine the change in definition of the heroes in Hindi films over a period of time. The researcher will conduct the content analysis of ten purposively selected films from the Hindi Cinema.